1995
DOI: 10.1111/j.1349-7006.1995.tb03095.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐level Expression of the CD44 Variant Sharing Exon v10 in Renal Cancer

Abstract: To examine whether renal cell carcinoma displays altered CD44 expression we performed reverse transcription‐polymerase chain reaction (RT‐PCR) analysis of CD44 in 38 specimens from renal cancer, normal kidney and metastases of 19 patients and 6 renal cancer cell lines. To detect the CD44 variants, we utilized the RT‐PCR Southern blot method. One out of 19 (5.3%) renal cancer specimens expressed a larger molecular weight band than 1 kb by RT‐PCR analysis, in contrast to previous findings in colon and breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Many studies have linked the expression of CD44 isoforms to tumour progression and metastatic capability in human malignant diseases, such as gastrointestinal cancer, 8,17–21 cervical cancer, 22–25 renal cancer, 26,27 non‐Hodgkin's lymphoma, 18,28–31 neuroblastoma, 32,33 and breast cancer 15,28 , 34–40 . There is also some direct experimental support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have linked the expression of CD44 isoforms to tumour progression and metastatic capability in human malignant diseases, such as gastrointestinal cancer, 8,17–21 cervical cancer, 22–25 renal cancer, 26,27 non‐Hodgkin's lymphoma, 18,28–31 neuroblastoma, 32,33 and breast cancer 15,28 , 34–40 . There is also some direct experimental support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CD44 is up‐regulated and expands its repertoire of variant isoforms in many human tumours [12–14]. Our previous study [23] showed that there are quantitative and qualitative differences in the expression of CD44 between renal cancer and normal kidney tissue, and among different renal cancer tissues. Using RT‐PCR‐Southern blot analysis, the CD44 variant sharing only exon v10 was enhanced in 71% of clear‐cell renal cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, there have been few studies of CD44 and its variants in RCC, or of their role in tumour progression. Studies to date have shown that CD44 isoform v10 (CD44v10) is expressed at high levels in renal cancer tissue [23] and there are clear differences in CD44 expression in the two major histological subtypes of RCC (clear-cell and chromophilic carcinoma) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies demonstrated that exon v10 plays a role in promoting breast tumor development and progression [19], [20]. High-level expression of this exon, v10, was also reported in malignant renal cell carcinoma cells [21]. Although the mechanisms by which exon v10 facilitates these processes are not entirely clear, it is possible that this exon stimulates migration, adhesion, and growth in microenvironments through mediating the interaction with ECM directly or indirectly by forming molecular complexes with other cell surface molecules.…”
Section: Introductionmentioning
confidence: 89%